Luto materno e o vínculo com o filho substituto - Sanches, Vânia de Mello Catelan (2012)
This work sought the understanding of maternal grief and the aspects that could bring complications to this process. It was considered the nature of the link that would structure between the mother and the replacement child, or rather, the son who was born to soften the pain for the loss of another son and the methodology used was the case study. John Bowlby´s Attachment Theory explains the process of making and breaking of affection bonds, as well as the characteristics of these links. The way each person constructs his/her internal working model, based on the kind of attachment that was developed in early childhood under the influence of the caregivers, determines the way each one will face the difficulties that life brings. The study led to the understanding that mothers with ambivalent and insecure attachments would be more likely to seek a new pregnancy to relieve the pain of loss. The link with the replacement child might be imbued image and influence of the dead child, causing, in some cases, damage to the child's identity